Loss of Adult Cardiac Myocyte GSK-3 Leads to Mitotic Catastrophe Resulting in Fatal Dilated Cardiomyopathy. Issue 8 (15th April 2016) - Zhou, Jibin; Ahmad, Firdos; Parikh, Shan; Hoffman, Nichole E.; Rajan, Sudarsan; Verma, Vipin K.; Song, Jianliang; Yuan, Ancai; Shanmughapriya, Santhanam; Guo, Yuanjun; Gao, Erhe; Koch, Walter; et al.
Abstract : Rationale: : Cardiac myocyte–specific deletion of either glycogen synthase kinase (GSK)-3α and GSK-3β leads to cardiac protection after myocardial infarction, suggesting that deletion of both isoforms may provide synergistic protection. This is an important consideration because of the fact that all GSK-3–targeted drugs, including the drugs already in clinical trial target both isoforms of GSK-3, and none are isoform specific. Objective: : To identify the consequences of combined deletion of cardiac myocyte GSK-3α and GSK-3β in heart function. Methods and Results: : We generated tamoxifen-inducible cardiac myocyte–specific mice lacking both GSK-3 isoforms (double knockout). We unexpectedly found that cardiac myocyte GSK-3 is essential for cardiac homeostasis and overall survival. Serial echocardiographic analysis reveals that within 2 weeks of tamoxifen treatment, double-knockout hearts leads to excessive dilatative remodeling and ventricular dysfunction. Further experimentation with isolated adult cardiac myocytes and fibroblasts from double-knockout implicated cardiac myocytes intrinsic factors responsible for observed phenotype. Mechanistically, loss of GSK-3 in adult cardiac myocytes resulted in induction of mitotic catastrophe, a previously unreported event in cardiac myocytes. Double-knockout cardiac myocytes showed cell cycle progression resulting in increased DNA content and multinucleation. However, increased cell cycle activity was rivaled by marked activation of DNA damage, cell cycle checkpoint activation, and mitotic catastrophe–induced apoptotic cell death. Importantly, mitotic catastrophe was also confirmed in isolated adult cardiac myocytes. Conclusions: : Together, our findings suggest that cardiac myocyte GSK-3 is required to maintain normal cardiac homeostasis, and its loss is incompatible with life because of cell cycle dysregulation that ultimately results in a severe fatal dilated cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.